That Old Time Religion: Christianity and Black Economic Progress After Reconstruction - Luke Petach (Global Labor Organization (GLO), 2024)
This paper studies the effect of religion on the economic progress of Black Americans after Reconstruction. Southern religious institutions-particularly the Southern Baptist church-played a key role in the development of the Lost Cause mythology that helped legitimate the white supremacist political order which dominated the American South well into the twentieth century. Using county-level data on religious adherence from the 1860 Census and data on county economic characteristics from the full count Census for the years 1850 to 1910, I show that from 1870 onward Black incomes, Black literacy rates, the share of Black individuals with "high-skill" occupations, and the share of Black individuals with manufacturing occupations were lower in counties with a greater pre-Civil War Baptist membership share. This finding is robust to county-fixed effects, year-fixed effects, state-specific linear time trends, and controlling for the county slave population share prior to 1860. No such negative effect on Black economic outcomes exists for the Catholic church, which never formally recognized the Confederacy. I highlight the relationship between Baptist church membership and Lost Cause ideology by demonstrating a positive effect of Baptist membership on Confederate monument construction, lynching, and showings of D.W. Griffith's Birth of a Nation.
Keywords: Z12; Z13; J15; N31; 330; Economics of Religion; Stratification Economics; Economic History; Post- Reconstruction; Lost Cause